2020
DOI: 10.1186/s12943-020-01216-3
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of RNA modification N6-methyladenosine in human cancer

Abstract: Since the breakthrough discoveries of DNA and histone modifications, the field of RNA modifications has gained increasing interest in the scientific community. The discovery of N6-methyladenosine (m6A), a predominantly internal epigenetic modification in eukaryotes mRNA, heralded the creation of the field of epi-transcriptomics. This post-transcriptional RNA modification is dynamic and reversible, and is regulated by methylases, demethylases and proteins that preferentially recognize m6A modifications. Altered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
198
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(198 citation statements)
references
References 159 publications
0
198
0
Order By: Relevance
“…The abnormal expression of m6A “writer” proteins results in abnormal levels of m6A modification in tumor cells, which further abnormalizes the metabolism of tumor-related genes mRNA, thereby promoting the development of a variety of cancers ( 8 , 9 ). The up-regulated METTL3 in gastric cancer was positively correlated with the poor prognosis of patients, and METTL3 promoted epithelial–mesenchymal transition of gastric cancer, leading to tumor invasion and metastasis ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…The abnormal expression of m6A “writer” proteins results in abnormal levels of m6A modification in tumor cells, which further abnormalizes the metabolism of tumor-related genes mRNA, thereby promoting the development of a variety of cancers ( 8 , 9 ). The up-regulated METTL3 in gastric cancer was positively correlated with the poor prognosis of patients, and METTL3 promoted epithelial–mesenchymal transition of gastric cancer, leading to tumor invasion and metastasis ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that m 6 A modi cation is involved in many biological processes in mammals, including mRNA splicing, export, localization, translation, and stability [44]. Moreover, the m 6 A methylation of several associated proteins has been closely related to tumorigenesis in a broad range of cancer types [45]. As a "writer" in the m 6 A methyltransferase complex, METTL3 has been shown to affect various biological behaviors and, in turn, mediate carcinogenesis and development.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, a number of noncoding RNAs and their functional mechanisms have been identified and characterized in most types of cancer [ 3 , 4 ]. The modifications of genomic DNA and RNA also provide new insight into the functional mechanisms of nucleic acids in cancer [ 5 , 6 , 7 , 8 ]. Various DNA modifications regulate the expression of coding and noncoding genes beyond the traditional gene regulation mechanism through transcription factors [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Various DNA modifications regulate the expression of coding and noncoding genes beyond the traditional gene regulation mechanism through transcription factors [ 6 , 7 ]. Moreover, the RNA modifications modulate the functional activity of coding and noncoding RNAs [ 5 , 8 ]. Therefore, the scientific view of DNA and RNA as generators and by-products of proteins has been changing.…”
Section: Introductionmentioning
confidence: 99%